Intrinsic protein disorder uncouples affinity from binding specificity. (26th October 2022) - Lazar, Tamas; Tantos, Agnes; Tompa, Peter; Schad, Eva
Abstract: Intrinsically disordered proteins (IDPs) and intrinsically disordered regions (IDRs) of proteins often function by molecular recognition, in which they undergo induced folding. Based on prior generalizations, the idea prevails in the IDP field that due to the entropic penalty of induced folding, the major functional advantage associated with this binding mode is "uncoupling" specificity from binding strength. Nevertheless, both weaker binding and high specificity of IDPs/IDRs rest on limited experimental observations, making these assumptions more speculations than evidence‐supported facts. The issue is also complicated by the rather vague concept of specificity that lacks an exact measure, such as the K d for binding strength. We addressed these issues by creating and analyzing a comprehensive dataset of well‐characterized ID/globular protein complexes, for which both the atomic structure of the complex and free energy (Δ G, K d ) of interaction is known. Through this analysis, we provide evidence that the affinity distributions of IDP/globular and globular/globular complexes show different trends, whereas specificity does not connote to weaker binding strength of IDPs/IDRs. Furthermore, protein disorder extends the spectrum in the direction of very weak interactions, which may have important regulatory consequences and suggest that, in a biological sense, strict correlation of specificity and binding strength are uncoupled by structural disorder.